Effect of pH, anions and cations on the dissolution kinetics of humic acid particles - Brigante, Maximiliano Eduardo (2009)
The dissolution kinetics of solid humic acid (HA) particles under different conditions is reported and analyzed. The dissolution rate at pH 4 and 5 is very slow and several years may take to achieve equilibration. The rate is strongly increased by increasing pH, and at pH 11 complete dissolution is achieved in 30 min. The dissolution rate is also markedly increased by the presence of monocarboxylic acids and anionic herbicides such as glyphosate and 2,4-D. On the contrary, the rate is decreased by inorganic divalent cations (Mg2+, Ca2+, Sr2+, Ba2+). The divalent cation paraquat has a dual behavior, decreasing the dissolution rate at pH >7 but increasing it at pH <7. Simple modeling assuming a surface-controlled dissolution kinetics can reproduce reasonably well the effects of anions and cations. The different ions seem to affect the dissolution rate by modifying intermolecular forces between HA molecules located at the surface of the particles. © 2009 Elsevier B.V. All rights reserved.